2014
DOI: 10.5935/0103-507x.20140041
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Activities Score and workload in the intensive care unit of a university hospital

Abstract: ObjectiveThe nursing workload consists of the time spent by the nursing staff to perform the activities for which they are responsible, whether directly or indirectly related to patient care. The aim of this study was to evaluate the nursing workload in an adult intensive care unit at a university hospital using the Nursing Activities Score (NAS) instrument.MethodsA longitudinal, prospective study that involved the patients admitted to the intensive care unit of a university hospital between March and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
50
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 26 publications
11
50
0
15
Order By: Relevance
“…(4,13) A lower mean in the NAS was found, compared to other Brazilian studies, which found results ranging from 73.4 to 87.5%. (15) However, other studies showed similar NAS means, ranging from 52.7% to 66.1%. These results probably reflect a profile of the patients similar to the ICU in this study.…”
Section: Discussionmentioning
confidence: 87%
“…(4,13) A lower mean in the NAS was found, compared to other Brazilian studies, which found results ranging from 73.4 to 87.5%. (15) However, other studies showed similar NAS means, ranging from 52.7% to 66.1%. These results probably reflect a profile of the patients similar to the ICU in this study.…”
Section: Discussionmentioning
confidence: 87%
“…In the literature, there is great variation of NAS score relative to patients admitted to ICU of public hospitals (19)(20) . Considering critical patients that developed infection during stay in ICU, some authors obtained a mean NAS of 81.2+16.2% (6) .…”
Section: Discussionmentioning
confidence: 99%
“…Although the NAS is widely used in intensive care units (ICU) of different specialties (7)(8)(9) , its application in specific settings, such as postoperative care of cardiac surgery, is still limited (10)(11) . The NAS findings have indicated that sociodemographic (6)(7) and clinical variables, (7) length of stay in the ICU (11) , mortality (8) and severity of the patient's conditions (8,10,12) are factors associated with the high workload of the nursing staff. Studies conducted with patients in the postoperative period of cardiac surgery showed that, in the first 24 hours, the nursing workload ranged from 61.6% to 96.8% (10)(11)(12)(13) .…”
Section: Introductionmentioning
confidence: 99%
“…The NAS findings have indicated that sociodemographic (6)(7) and clinical variables, (7) length of stay in the ICU (11) , mortality (8) and severity of the patient's conditions (8,10,12) are factors associated with the high workload of the nursing staff. Studies conducted with patients in the postoperative period of cardiac surgery showed that, in the first 24 hours, the nursing workload ranged from 61.6% to 96.8% (10)(11)(12)(13) . In addition, the authors observed that, in this population, the NAS was associated with adverse outcomes such as increased length of stay in the ICU, complications and mortality (13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%